2019
DOI: 10.1002/brb3.1264
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies as moderating factors to compassion fatigue among critical care nurses

Abstract: Purpose This study measured levels of compassion fatigue, burnout and satisfaction among critical care and emergency nurses. It investigated coping strategies as moderating factors and as predictors to levels of compassion fatigue. Methods Using a cross–sectional design, this study was conducted on 228 (84.4%) out of 270 from four Jordanian hospitals. Nurses worked in different types of critical care units and emergency departments. Nurses completed a demographic questionnaire on the professional quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
65
3
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 41 publications
13
65
3
14
Order By: Relevance
“…Nurses complained about the poor impression and inappropriate appreciation of society towards nursing profession and physician-centered issue in the organization and even society, and both of them were considered to be effective in creating CF from the nurses' point of view. In line with this, Barmawi et al noticed that level of social support among nurses is low to medium and must to be improved (31). Barr(2017) concluded that perceived social support had important direct and indirect relationships with CF in nurses (32).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Nurses complained about the poor impression and inappropriate appreciation of society towards nursing profession and physician-centered issue in the organization and even society, and both of them were considered to be effective in creating CF from the nurses' point of view. In line with this, Barmawi et al noticed that level of social support among nurses is low to medium and must to be improved (31). Barr(2017) concluded that perceived social support had important direct and indirect relationships with CF in nurses (32).…”
Section: Discussionmentioning
confidence: 86%
“…An important nding that emerged in this study was the inappropriate and poor impression toward nurses in the society and in turn physician-centeredness in the health care systems and consequently they showed that it could be a factor in creating mental fatigue. Barmawi et al (2019) also mentioned low to moderate levels of social support in their study (31). Nurses complained about the poor impression and inappropriate appreciation of society towards nursing profession and physician-centered issue in the organization and even society, and both of them were considered to be effective in creating CF from the nurses' point of view.…”
Section: Discussionmentioning
confidence: 95%
“…Nurses whose perceived SS score was higher were characterized by a lower level of BO (p = 0.002; r = -0.236) and in the case of family support a lower level of CF (p= -0.17, r = 0.02) [28]. In other studies, it was proved that higher CS was shown by nurses who sought SS (p = 0.011) [29]. [30].…”
Section: Discussionmentioning
confidence: 93%
“…The second aim was to study the effect of coping on mood and fatigue. It has been shown that higher mean scores in problem-solving, avoidance, and seeking social support were associated with higher levels of compassion fatigue [ 40 ]. Thus, the question remains as to whether the coping strategy previously used or accumulated over time affects the mood and fatigue of nurses.…”
Section: 1 Aim/research Questionsmentioning
confidence: 99%